Innovations in the management of Wilms' tumor. (August 2014) - Gleason, Joseph M.; Lorenzo, Armando J.; Bowlin, Paul R.; Koyle, Martin A.
Advances in the management of Wilms' tumor have been dramatic over the past half century, not in small part due to the institution of multimodal therapy and the formation of collaborative study groups. While different opinions exist in the management of Wilms' tumors depending on where one lives and practices, survival rates have surpassed 90% across the board in Western societies. With more children surviving into adulthood, the concerns about morbidity have reached the forefront and now represent as much a consideration as oncologic outcomes these days. Innovations in treatment are on the horizon in the form of potential tumor markers, molecular biological means of testing for chemotherapeutic responsiveness, and advances in the delivery of chemotherapy for recurrent or recalcitrant tumors. Other technological innovations are being applied to childhood renal tumors, such as minimally invasive and nephron-sparing approaches. Risk stratification also allows for children to forego potentially unnecessary treatments and their associated morbidities. Wilms' tumor stands as a great example of the gains that can be made through protocol-driven therapy with strenuous outcomes analyses. These gains continue to spark interest in minimization of morbidity, while avoiding any compromise in oncologic efficacy. While excitement and innovation are important in the advancement of treatment delivery, we must continue to temper this enthusiasm and carefully evaluate options in order to continue to provide the highest standard of care in the management of this now highly curable disease.